Hybrid Curriculum Model in a State Madrasah: A Case Study of Centralized and Decentralized Practices at MTsN 1 Malang - Ikhwanul Habib; Taqiyuddin Kabalmay (Kitaba, 2026)
Curriculum models play a crucial role in determining the quality and direction of education. However, the implementation of centralized and decentralized curricula often presents challenges in balancing national standards with local needs. This study aims to analyze the application of a hybrid curriculum model at MTsN 1 Malang City, an Indonesian state madrasah that integrates both centralization and decentralization mechanisms. Using a qualitative descriptive approach, data were collected through semi-structured interviews with three key informants (the madrasah head, vice principal for curriculum, and a senior teacher), participatory observations of curriculum practices, and document analysis of curriculum guidelines and lesson plans. The findings reveal that centralization is realized through compliance with national standards set by the Ministry of Religious Affairs and the Ministry of Education, Culture, Research, and Technology, ensuring uniformity in core subjects, learning outcomes, and assessment frameworks. Decentralization is manifested through locally initiated innovations, including the establishment of Ma'had Al-Madany (a student dormitory program), the development of special class programs (Bilingual, Tahfidz, and Olympic classes), and the initiation of Project-Based Learning, all of which accommodate students' interests, talents, and contextual needs. Teachers play a dual role in this hybrid model: as implementers of centralized policies and as innovators within decentralized spaces. The novelty of this study lies in its detailed empirical illustration of how a hybrid curriculum model operates in a madrasah context by systematically mapping the interaction between dual ministerial regulations and locally driven innovations. Unlike previous studies that tend to discuss curriculum centralization and decentralization separately, this research demonstrates a practical framework for harmonizing national policies with contextual educational creativity in Islamic secondary education. The study concludes that the hybrid curriculum model at MTsN 1 Malang represents a strategic approach to improving madrasah education quality through balanced integration of central regulation and local innovation, with implications for curriculum policy, school leadership, and teacher professional development.